A multi-national validity analysis of the self-perceived communication competence scale. Issue 1 (2nd January 2020) - Croucher, Stephen M.; Kelly, Stephanie; Rahmani, Diyako; Burkey, Mark; Subanaliev, Talgat; Galy-Badenas, Flora; Lando, Agnes Lucy; Chibita, Monica; Nyiransabimana, Venantie; Turdubaeva, Elira; Eskiçorapçı, Nadirabegim; Jackson, Kelsea
ABSTRACT: The self-perceived communication competence (SPCC) measure has been used in over 50 published studies since 2000. McCroskey and McCroskey (1988. Self-report as an approach to measuring communication competence. Communication Research Reports, 5, 108–113. doi: 10.1080/08824098809359810 ) developed the measure to be used within the US college/university classroom. Despite its intended use, the measure is frequently used outside of the US and outside of the college/university setting without tests of measurement invariance. In fact, only four studies have performed tests of internal consistency on the measure since 2000, and each has found poor fit. Therefore, the purpose of this study was to assess the utility of the measure outside of its intended population. The measure was utilized to survey respondents from 12 countries and failed to yield acceptable fit statistics in all samples, showing poor evidence of construct validity.